New bibliographic style for the Cuban Journal of Agricultural science based on Harvard referencing - Lok, Sandra; Cervantez, Rafael (Cuban Journal of Agricultural Science, 2016)
As part of the updates made by the Cuban Journal of Agricultural Science for a more efficient management of its publications, it was decided by the Editorial Board to update the bibliographic style (how to place quotations in the text and the corresponding bibliographical references) , according to the style guidelines of Harvard referencing . The main intention of the changes is to increase the veracity of the information that is published and to guarantee the traceability of the used documents.